2017
DOI: 10.3354/cr01459
|View full text |Cite
|
Sign up to set email alerts
|

Future forest distribution on Finnmarksvidda, North Norway

Abstract: Finnmarksvidda is Norway's largest mountain plateau, located in the Arctic/alpineboreal transition area. The area is also a central winter grazing area for the reindeer herds of the indigenous Sámi people. This study develops a bioclimatic-based model to simulate future potential vegetation, with a focus on forest types. The model utilizes a bioclimatic study in the region, where vegetation types have been grouped according to minimum summer temperature demands. This is then used as a base for modelling of fut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…They showed that the relationship between the NDVI and interannual temperature variability has weakened substantially in the northern mid and high latitudes since 1980, possibly due to extreme climate events. Indeed, temperature rise increases the frequency of extreme weather events, droughts, wind storms and wildfires, and hence may cause severe, long‐term damage to forest ecosystems, by enhancing the forest vulnerability to insects, pests or fungus pathogen attacks (Bryn & Potthoff, 2018; Hofgaard et al, 2012; Karlsen et al, 2017; Morin et al, 2018). Unlike for agricultural lands, where the spectral response to the influencing factor is quick, in the case of forests this process might be very extended in time, so a significant time lag in correlation between NDVI and meteorological element can occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that the relationship between the NDVI and interannual temperature variability has weakened substantially in the northern mid and high latitudes since 1980, possibly due to extreme climate events. Indeed, temperature rise increases the frequency of extreme weather events, droughts, wind storms and wildfires, and hence may cause severe, long‐term damage to forest ecosystems, by enhancing the forest vulnerability to insects, pests or fungus pathogen attacks (Bryn & Potthoff, 2018; Hofgaard et al, 2012; Karlsen et al, 2017; Morin et al, 2018). Unlike for agricultural lands, where the spectral response to the influencing factor is quick, in the case of forests this process might be very extended in time, so a significant time lag in correlation between NDVI and meteorological element can occur.…”
Section: Discussionmentioning
confidence: 99%
“…The global warming observed over the past decades has an impact on increased evapotranspiration and water shortage that consequently increase the severity and duration of droughts worldwide (Dai, 2013; Forzieri et al, 2017). Numerous studies (Forzieri et al, 2016; Haarsma et al, 2013) reported that climate change may increase the frequency of extreme weather events, not only droughts, but also devastating wind storms and wildfires in many regions, and hence may cause severe, long‐term damage to forest ecosystems (Bryn & Potthoff, 2018; Hofgaard et al, 2012; Karlsen et al, 2017; Morin et al, 2018). The prolonged and repeatable severe weather conditions—like droughts—gradually impact the forest structure, enhancing the forest vulnerability to insects, pests or fungus pathogen attacks.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of the lengthening growing seasons, forests will become more dense and expand northwards and to higher elevations (Karlsen et al 2017). Climate models predict that pronounced increases in temperature and precipitation could transform more than half of the tundra into shrublands before the next century (Pearson et al 2013).…”
Section: Impacts and Strategies In Summermentioning
confidence: 99%
“…The influence of climate change on vegetation, especially on forest conditions, is highlighted in several studies (Buras et al, 2020;Schuldt et al, 2020;Prȃvȃlie et al, 2022;Yang et al, 2019;Liu et al, 2015). It has the potential to cause severe, long-term damage to forest ecosystems by increasing the frequency of extreme weather events, such as droughts, destructive windstorms and wildfires in many regions (Bryn and Potthoff, 2018;Hofgaard et al, 2012;Karlsen et al, 2017;Morin et al, 2018). That is why monitoring vegetation dynamics and precisely characterising the response of vegetation to changing climate is essential in or-der to maintain a sustainable environment (Tomlinson et al, 2011;Barbosa et al, 2019).…”
Section: Introductionmentioning
confidence: 99%